2015
DOI: 10.1002/acr.22416
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk and Acute Coronary Syndrome in Giant Cell Arteritis: A Population‐Based Retrospective Cohort Study

Abstract: Objective We assessed the occurrence of acute coronary syndrome (ACS) in patients with giant cell arteritis (GCA) compared to subjects without GCA. Methods We retrospectively reviewed a population-based incidence cohort of Olmsted County, Minnesota residents with GCA diagnosed in 1950-2009. We compared this cohort with a cohort of patients without GCA of similar age, sex and calendar year from the same population. Results The study included 245 patients with GCA and 245 non-GCA subjects. Mean Framingham ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 18 publications
1
32
0
4
Order By: Relevance
“…However, the rate ratios compared with reference population were higher in the Canadian study. Udayakumar et al demonstrated no overall increased in the rate of acute coronary syndrome among patients with GCA (15). The association between GCA and coronary artery disease is unclear with varied findings among several population-based studies (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate ratios compared with reference population were higher in the Canadian study. Udayakumar et al demonstrated no overall increased in the rate of acute coronary syndrome among patients with GCA (15). The association between GCA and coronary artery disease is unclear with varied findings among several population-based studies (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Udayakumar et al demonstrated no overall increased in the rate of acute coronary syndrome among patients with GCA (15). The association between GCA and coronary artery disease is unclear with varied findings among several population-based studies (13)(14)(15). Differences in case ascertainment of cases of GCA (study criteria vs. biopsy-proven GCA) may explain such variations.…”
Section: Discussionmentioning
confidence: 99%
“…Риск ИБС был также по-вышен, но это повышение не достигало статистической значимости (1,20; 95% ДИ 1,00-1,44). По данным другого исследования, у больных ГКА не было выявлено повышения риска развития острого коро-нарного синдрома [22]. Ранее М. Durand и соавт.…”
Section: Discussionunclassified
“…Одно из не-давних исследований полностью подтверждает эти данные, за исключением более высокой частоты заре-гистрированных инсультов (7 %) [44]. Любопытные результаты были получены в недавнем ретроспектив-ном исследовании [45]. Было отмечено, что риск раз-вития острого коронарного синдрома у больных гиган-токлеточным артериитом сопоставим с таковым у пациентов, не страдающих данным заболеванием; наряду с этим у больных гигантоклеточным артериитом ряд традиционных факторов риска, таких как сахарный диабет, оказывали протективное действие.…”
Section: о б з о р ыunclassified